To solve this system of equations, we can add the two equations together:
d + e + (-d + e) = 1 + (-5)
e + e = -4
2e = -4
e = -2
Now that we have the value of e, we can substitute it back into one of the original equations to solve for d:
d + (-2) = 1
d = 3
Therefore, the ordered pair (d, e) is (3, -2).
The correct answer from the list of options is (3, -2).
Solve the system of equations and choose the correct answer from the list of options.
d + e = 1
−d + e = −5
Label the ordered pair as (d, e).
Group of answer choices
(−2, 3)
(3, −2)
(0, 0)
(−3, 0)
1 answer